MICROSTRUCTURE AND PROPERTIES OF HIGH CHROMIUM WHITE CAST IRONS ALLOYED WITH BORON (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The microstructure and mechanical properties of high chromium white cast iron with composition: 2,6÷3,4% C; 0,9÷1,1% Si; 0,8÷1,1% Mn; 1,0÷1,3% Mo; 12,3÷13,4% Cr, additionally doped with boron in an amount of 0,18% to 1,25% is investigated. The microstructure of six compositions of white cast irons is studied by means of an optical metallographic analysis - one without boron, and the others contain 0,18%; 0,23%; 0,59%; 0,96% and 1,25% boron. A test is performed to determine: hardness by the Rockwell method; microhardness; bending strength and impact toughness. It was found that at a boron content of 0,18%; 0,23% and 0,59%, the structure of white cast irons is subeutectic, with impact toughness in the range of 1,80÷1,52 J/cm2; with a boron content of 0,96%, the structure of white cast iron is close to the eutectic, with impact toughness 0,98 J/cm2 ; at a boron content of 1,25% the structure of white cast iron is supereutectic and the impact toughness decreases to 0,68 J/cm2. With a change in the boron content from 0,8% to 1,25%, the amount of carbide phase in the structure of white cast iron increases, which leads to an increase in hardness from 53 to 59 HRC. The highest bending strength (Rmi=660,85 MPa) was obtained in white cast irons with a boron content of 0,23%.